Género y Reconocimiento en el Ámbito Laboral. - Chávez Escobedo, Juan Manuel (Revista Daena: International Journal of Good Conscience, 2023)
In the present work I wish to address the issue from my professional background and personal experience in the workplace, currently it is very common for gender and recognition issues to be addressed from various perspectives in different fields, in this case it is necessary to touch on the subject with a labor perspective with the aim of promoting reflection in academic readers, students and researchers to contribute to the topic from a professional, academic perspective and with experiential support in the labor field.